Translating the Untranslatable¬: An Examination of Semantic Loss in the Translation of Bulleh Shah’s poetry - Muhammad Farrukh Sajjad; Anum Zahra; Kashif Raza (`, 2025)
The current research basically highlights the problems of translating Bulleh Shah’s poetry. It is explained how different translators of Bulleh Shah misunderstood the message conveyed by him. This paper’s importance lies in its assessment of both foreign and indigenous translations of his works. The scholars have scrutinized the chosen texts from his poems. After analyzing the textual data, it is evident their deviations have been made by both local and international interpreters from the meaning and sense of authorship itself. In addition to that, their translations do not catch up with what Bulleh Shah means semantically hence showing visible gaps compared to the source text. Our findings conclude that Shah’s profound philosophical ideas, use of metaphors as well as cultural and religious references make it impossible to render his poetry into English exactly which causes semantic losses especially while turning his religious thoughts expressed in verse. Keywords: Untranslatability, semantic loss, Bulleh Shah, religious and cultural metaphors